Designing Marketing Strategy for Bbq Dirumah using SWOT Analysis and IE Matrix - Arlieta Kirana Brahmaniswari; Sari Wulandar; Ima Normalia Kusmayanti (School of Industrial and System Engineering, Telkom University, 2022)
Bbq Dirumah is an MSME in the food sector that was established during the Covid-19pandemic in Indonesia so that sales have not had an increasing trend and have not reached thetarget. One of the problem is the marketing strategy that has not been carried out optimally.Therefore, it is necessary to propose a marketing strategy based on the condition of BbqDirumah SMEs in order to increase sales. SWOT analysis was conducted to determine internaland external factors as input in the preparation of the SWOT and IE matrix so that alternativestrategies were obtained and evaluation was carried out to prioritize alternative strategiesimplemented with QSPM as an effort to increase sales to achieve targets. The research objectiveis to design a marketing strategy for Bbq Dirumah to increase sales volume in order to achievethe predetermined target. The results showed that the position of MSME Bbq Dirumah was inquadrant V on the IE matrix with an IFE score of 2.604 and an EFE score of 2.684 so the rightstrategy is market penetration and product development. An alternative strategy based on thepriority value in the QSPM is